PERANCANGAN WEB PROFILE TANAMAN HIAS MENGGUNAKAN WEB NATIVE PADA CV BERIBENIH KOTA TANGERANG SELATAN - Mahdiaroji; Bagas Riyadi; Dzaki Rozaan; Suhanda Saputra (Journal of Research and Publication Innovation, 2023)
The role of information technology today cannot be separated from the times, information technology offers various conveniences, including in the world of commerce. In this research regarding the trading of ornamental plant equipment at CV BeriBenih. CV BeriBenih still does not have promotional media which results in less than optimal business processes. So the company has difficulty in attracting new customers and partners. In this condition, BeriBenih company created a web-based company profile. Company Profiles are often used to promote their brand, attract new prospects or clients, and build a strong reputation in the marketplace. From the results we got from this research, it really helped CV BeriBenih to increase promotions and attract new customers and even provide opportunities to attract new clients.